Load Frequency Control of Single Area System Using Ziegler-Nichols and Genetic Algorithm - Praveena, P.; Shubhanka, H. S.; V. Neha; Prasath, P.; Veda, G. S. (Asian Journal of Electrical Sciences, 2019)
In this paper, determining the optimal proportional-integral-derivative (PID) controller gains of load frequency control (LFC) system using Ziegler-Nichols (ZN) and Genetic algorithm (GA) is presented. The conventional tuning of PID is difficult as the system and the load parameters change constantly. It is for this reason tuning strategies has been applied. Comparative studies of both the techniques are presented. The simulation has been conducted in MATLAB Simulink package for single area power system.